Papua New Guinea Economic Update, July 2019 : Recovery Amid Uncertainty - World Bank Group (World Bank, Washington, DC, 2019)
Papua New Guinea’s (PNG) economy has started recovering from a series of external shocks, but its growth outlook remains fragile due to rising uncertainties. The recovery is being observed in the resource sector, mainly in its extractive segment dominated by liquefied natural gas (LNG), while growth in the non-resource economy remains subdued due to sluggish domestic demand. A longer-term government agenda of building an inclusive and sustainable economy will require a focus on structural reforms. It also looks at sector-specific issues and identifies a set of implementation actions for each priority sector. Agriculture is one of the priority sectors due to its large share of the economy and the vast population living in rural areas that is involved in subsistence and cash income agriculture. To realize the potential of agriculture as a source of income and job creation, the authorities should consider policy options and responses that will secure sustainable rural livelihoods in food and agriculture, as discussed in the report.